THE IMPLEMENTATION OF MAKE A MATCH METHOD TO TEACH QURAN HADITH IN THE TOPIC OF WRITING HIJAIYYAH LETTERS - Rohmutadi Rohmutadi (Tadibia Islamika, 2021)
The research objectives were 1) to analyze the activeness and learning achievement of students in the subject of the Qur'an Hadith at MI Al IkhsanUjungnegoro, Kandeman District, Batang Regency before the implementation of the Make and Match learning model. 2) Analyzing the implementation of the Make and Match learning model in the subject of the Al-Quran Hadith to increase the activeness and achievement of learning to write hijaiyah letters at MI Al-IkhsanUjungnegoro, Kandeman District, Batang Regency. 3) Analyzing the implications of implementing the Make and Match learning model in the subject of Al-Qur’an Hadith to increase the activeness and achievement of learning to write hijaiyah letters at MI Al-IkhsanUjungnegoro, Kandeman District, Batang Regency. The approach used in this study is a qualitative approach. field research (field research) because this research was conducted in the realm of life, namely by observing directly the teaching and learning activities of Al-Qur'an hadith subjects on the material of writing hijaiyah letters of MI Al-IkhsanUjungnegoro students, Kandeman District, Batang Regency. The results of the study: 1) The activeness and learning achievement of students in the subject of the Qur'an Hadith at MI Al-IkhsanUjungnegoro, Kandeman District, Batang Regency before the implementation of the Make and Match learning model can be said to be lacking. 2) In the realm of implementation, there are (1) Preparation Phase, (2) Implementation Phase, (3) Assessment Phase, (4) Closing Phase. 3) The implications of implementing the Make and Match learning model in the subject of Al-Quran Hadith to increase the activeness and achievement of learning to write hijaiyah letters at MI Al IkhsanUjungnegoro, Kandeman District, Batang Regency are good.